Microplastics and Nanoplastics in Cardiovascular Disease: An Emerging Cardiovascular Risk Factor - Alberto Polimeni; Domenico Simone Castiello; Rossella Quarta; Tommaso Gori; Giovanni Martino; Letizia Rosa Romano; Federica Meringolo; Giovanni Lopes; Masakazu Yasuda; Ciro Indolfi; Antonio Curcio (Cardiovascular Toxicology, 2026)
Microplastics and nanoplastics (MNPs) have become pervasive contaminants in air, water, and food, leading to continuous human exposure. Contrary to the long-standing assumption that these particles are biologically inert, accumulating evidence now shows that MNPs cross epithelial and endothelial barriers, circulate systemically, and accumulate in cardiovascular tissues. Experimental, translational, and early clinical studies demonstrate that some MNPs can induce oxidative stress, endothelial dysfunction, mitochondrial injury, immune activation, and coagulation pathway dysregulation, mechanisms that converge on atherosclerotic development and progression, plaque destabilization, atherothrombosis, and cardiac remodeling. Recent human data identifying MNPs in carotid and coronary plaques, arterial specimens, thrombi, and cardiac tissues provide direct proof-of-concept for their cardiovascular involvement. These findings position MNPs as an emerging cardiovascular risk factor, with implications for prevention, patient risk stratification, and environmental health policy. Major knowledge gaps remain, including the absence of standardized biomarkers of exposure, dose–response quantification, and longitudinal clinical cohorts. Recognizing environmental plastics as cardiovascular toxins demands urgent, multidisciplinary investigation and integration of environmental exposure into cardiovascular disease prevention frameworks. Graphical Abstract Overview of exposure routes and subsequent pathophysiological mechanisms of microplastics and nanoplastics leading to cardiovascular disease scenarios.

Estimation of the Acute Myocardial Infarction Onset Time based on Time-Course Acquisitions - Anna Procopio; Salvatore De Rosa; Caterina Covello; Alessio Merola; Jolanda Sabatino; Alessia De Luca; Christoph Liebetrau; Christian W. Hamm; Ciro Indolfi; Francesco Amato; Carlo Cosentino (Annals of Biomedical Engineering, 2021)

Model and Application to Support the Coronary Artery Diseases (CAD): Development and Testing - Lina Teresa Gaudio; Pierangelo Veltri; Salvatore De Rosa; Ciro Indolfi; Gionata Fragomeni (Interdisciplinary Sciences: Computational Life Sciences, 2020)